Profil Elektrolit Serum Pedet Sapi yang Diinfeksi Escherichia coli K-99 dan Diberi Mikrokapsul Imunoglobulin-G Anti E. coli - Mihardi, Arief Purwo; Esfandiari, Anita; Widhyari, Sus Derthi; Murtini, Sri (Jurnal Veteriner; Vol 20 No 2 (2019), 2019)
Escherichia coli (E. coli) K-99 infection cause acute diarrhea in calves which may reduce electrolyte, such as sodium and potassium.  The experiment was conducted to study the sodium and potassium profiles in calves infected by E. coli and received immunoglobulin G anti E. coli K99 microcapsules.  Sixteen calves, 4 – 6 days years old, were grouped into four groups, consists of four calves, i.e. negative control/NC group (the calves were not infected by E. coli K-99 and no treatments); positive control/PC group (the calves were infected by E. coli K-99 and no treatments); treatment 1/P1 group (the calves were infected by E. coli K-99 and received colostrum suspension of IgG anti E. coli K-99); and treatment 2/P2 group (the calves were infected by E. coli K-99 and received microcapsules of IgG anti E. coli K-99).  Escherichia coli K-99 were infected to all calves except the NC group orally with the dosage of 5 × 1010 cfu/ml.  Suspension and microcapsules of IgG anti E. coli K-99 for each calf were given orally with dosage of 1.76 gram IgG anti E. coli K-99 per day.  Serum were collected from jugular vein at 0, 24, 48, 72, and 168 hours after E. coli K99 infection. The sodium and potassium concentrastion were analyzed using a spectrophotometer. Results of the experiment indicated that the concentration of sodium and potassium were not significantly different among groups.  Sodium concentration of P2 group was relatively higher than PC or P1 and showed increased concentration 168 hours after infection.  Potassium concentration of P2 were higher than the PC group, but lower than NC and P1 group.  In conclusion, the administration of IgG anti E. coli K-99 microcapsules was not significantly change the sodium and potassium concentration, but may maintain the stability of sodium level in calves infected by E. coli K-99.